Irradiation damage in (Zr0.25Ta0.25Nb0.25Ti0.25)C high-entropy carbide ceramics. (15th August 2020) - Wang, Fei; Yan, Xueliang; Wang, Tianyao; Wu, Yaqiao; Shao, Lin; Nastasi, Michael; Lu, Yongfeng; Cui, Bai
Abstract: This research revealed the mechanisms of irradiation damage in the novel high entropy ceramic materials. (Zr0.25 Ta0.25 Nb0.25 Ti0.25 )C high-entropy carbide ceramics (HECC) with a single-phase rock-salt structure was synthesized by spark plasma sintering, which was irradiated by 3 MeV Zr ions to 20 dpa at 25, 300, and 500 °C. X-ray diffraction analysis showed that (Zr0.25 Ta0.25 Nb0.25 Ti0.25 )C maintained a high phase stability without phase transformation after irradiation. About 0.2% lattice parameter expansion was revealed. The irradiation-induced microstructures were comprised of defect clusters with diameters of several nanometers, without void formation or radiation-induced segregation. The defect clusters were characterized by transmission electron microscopy as two types of dislocation loops, including perfect loops with Burgers vectors of b = a /2<1 1 0> and faulted Frank loops with Burgers vectors of b = a /3<1 1 1>. The growth of dislocation loops may be suppressed by the strong local lattice distortion. Nanoindentation tests showed irradiation-induced hardness increase, which was possibly caused by dislocation loops and lattice strain. Overall, the high irradiation resistance, along with other excellent physical properties makes HECC promising structural materials for advanced reactor designs. Graphical abstract: Image, graphical abstract